ADOPSI INOVASI TANAMAN MANGGIS DI KABUPATEN PANDEGLANG PROVINSI BANTEN - Mulyaningsih, Asih; Rohmawati, Imas; Suherna, Suherna (Jurnal Pengabdian Dinamika, 2016)
Mangosteen is one of commodities seeded fruit Banten Provincial government that has high selling values .Pandeglang Regency , especially district the performances , labuan , carita, pagelaran and banjar is one of the producer region manggis large enough .The purpose of research is draw up specific location technology based on a pattern maintenance plant manggis in module , produce seed manggis local superior ( 100 seeds ) , socialize and development pattern mangosteen vocational school at the center for the other manggis ( 4 districts namely: district the performances , labuan , carita, pagelaran and banjar ). Research sites in district the performances , labuan , carita, pagelaran and banjar Regency pandeglang .The study sample was taken deliberately with the total sample 40 people farmers manggis taken from each group of tani. Research methodology implemented through fgds and socialization manggis a nursery plants. he results of the study are drafting module and seedling cultivation technology Mangosteen and mangosteen results of the field school where the modules and mangosteen seed is spread to four districts, with the hope of mangosteen farmers could do with nursery mangosteen seeds, of course supported by the module mangosteen cultivation technology. In addition, the existence of an indispensable extension of farmers in the mend.